On oscillation of certain second order damped differential equations - Xu, Zhiting (Utilitas Mathematica, 2009)
Some oscillation criteria are obtained for the second order damped differential equation (r(t)|y′(t)α-1y′(t))′ +P(t)|y′(t)|α-1y′(t) + q(t)f(y) = 0. These results extend, unify many of the known oscillation theorems in existing literature.